Pengembangan E-Modul IPA Berbasis STEM pada Topik Sistem Ekskresi Manusia - Jovialine Albertine Rungkat; Anggelina Jeujanan; Brian Ricard Wola; Zusje Wiesje Merry Warouw (Postgraduate, University of Mataram, 2023)
Teachers generally lack sufficient knowledge about STEM approaches, so teachers have difficulty developing STEM-based modules. Our research aims to develop a STEM-based science e-module on the human excretory system topic that is suitable for use by junior high school students. We use a type of research and development (R&D) concerning the Borg & Gall development model modified by Palilingan. Data collection techniques using interviews and questionnaires. The research instruments used interview sheets, product validation questionnaires, and product practicality questionnaires. The results showed that: (1) the validity test by learning media experts obtained a score of 98.33% and was included in the very valid category (no need for revision); (2) the validity test by subject matter experts shows a value of 99.17% and is included in the very valid category (no need for revision); and (3) limited trials in small groups show a value of 93.40% and are included in the very practical category. Based on the research that has been done, the STEM-based science e-module on the human excretory system topic that is suitable for use by junior high school students is appropriate for use by junior high school students.